Sistem Manajemen Bengkel Berbasis Web Menggunakan Metode Waterfall (Studi Kasus: Fam Auto) - Haekal Aqila, Haekal Aqila; Firda Salsabila Putri; Wasis Haryono (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Motor vehicle workshops need an information system that can help in managing services, customers, and spare parts stock. This study designs a web-based workshop management system with a case study at the Fam Auto workshop, which aims to improve operational efficiency and data transparency. The methodology used is the waterfall system development model with stages of analysis, design, implementation, and testing. The results of this study are a web-based application that is able to record service transactions, manage customer data, monitor inventory, and generate reports. This system is expected to replace the manual process that has been used at Fam Auto and make it easier for workshop owners to monitor operational activities in real-time.